2012
DOI: 10.1186/1477-7819-10-204
|View full text |Cite
|
Sign up to set email alerts
|

Granular cell tumors: a report of six cases

Abstract: Granular cell tumor is a soft tissue neoplasm that originates in the nervous system and arises at virtually any body site, but is mainly found in the skin, oral cavity or digestive tract. Most are benign and reportedly malignant cases are rare, occurring in only 1% or 2% of cases. We report on our findings in six patients who developed granular cell tumor in the mammary gland, esophagus, subcutaneous tissue and muscle. Of six patients, two had granular cell tumor located in the breast, two in the submucosa of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 20 publications
4
37
0
3
Order By: Relevance
“…Las células se distribuyen en láminas y nidos de tamaño variable, que parecen infiltrar los haces de colágeno y músculo 2,3,5,6,7 Los hallazgos microscópicos suelen ser suficientes pero la inmunohistoquímica es útil para confirmar el diagnóstico: presenta positividad para la proteína S-100 ( fig.3). También se ha descrito positividad para CD68, CD57 (Leu-7), enolasa neuronal específica, laminina, lecitina, HLA-DR, proteína básica de la mielina, y el antígeno carcinoembrionario (CEA), aunque hay casos CEA negativos 5,7 .…”
Section: Discussionunclassified
“…Las células se distribuyen en láminas y nidos de tamaño variable, que parecen infiltrar los haces de colágeno y músculo 2,3,5,6,7 Los hallazgos microscópicos suelen ser suficientes pero la inmunohistoquímica es útil para confirmar el diagnóstico: presenta positividad para la proteína S-100 ( fig.3). También se ha descrito positividad para CD68, CD57 (Leu-7), enolasa neuronal específica, laminina, lecitina, HLA-DR, proteína básica de la mielina, y el antígeno carcinoembrionario (CEA), aunque hay casos CEA negativos 5,7 .…”
Section: Discussionunclassified
“…Atypical and malignant granular cell tumors account for less than 2% of the granular cell tumors (4,5,6). These tumors primarily affect adults even though it may be found in children also (7).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are benign and reportedly malignant cases are rare (1 % or 2 %) [1]. It was first reported by Abrikossoff by the name of granular cell myoblastoma.and considered to be derived from muscle, due to its localization in tongue and pharynx in the first reported cases [2]. Studies using S100 staining and electron microscopy found that the tumor cells originate in Schwann cells of peripheral nerves [3,4].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Resection with adequate margins is necessary because the tumor has no capsule and is proliferation invasive [2]. However long-term risk for disease progression is low.…”
Section: Review Of Literaturementioning
confidence: 99%